"A Spirit of Bolshevism?": Perth's Water Crisis of the 1920s. (January 2020) - Gregory, Jenny
The early 1920s were a pivotal period in Perth's water history, marked by conflict over the inadequacies of the city's water supply. Only a small area of the city had reticulated water; most people relied on wells or rainwater tanks. Water shortages, particularly in new suburbs and higher districts, prompted the Western Australian Government to impose water restrictions. The press, local government authorities, and opposition politicians took the government to task, and officials and householders protested at public meetings. This article analyzes the causes of water shortages, the level of protest, tensions over the governance of the water supply, and the response of the state government. As on America's west coast in the same period, government decision making was often influenced by rural needs, but the role played by urban householders, with the support of the press and opposition politicians, was paramount in shaping new water supply systems for city dwellers.